The Reparations Controversy The Jewish State and German Money in the Shadow of the Holocaust 1951-195 - Sharett, Yaakov (De Gruyter, 2011)
This book about the reparations issue ("shilumim" in Hebrew) brings together selected protocols of all debates held regarding conducting negotiations with Germany. This is the first book documenting confidential protocols lately opened to the public. With the elaborate introduction by Yehiam Weitz, this book will serve as a basic textbook for an important chapter not only in Israeli and German history, but also in post-war history in general.